Дослідження динаміки змін координат референцних станцій мережі ZAKPOS - Янків-Вітковська, Л. М. (Видавництво Львівської політехніки, 2010)
Предложено использовать метод макромоделирования для исследования динамических изменений координат референтных станций. Для примера взята сеть станций ZAKPOS. Найдено оптимальные пути для высокоточного определения координат референтных станций сети. We suggest using the method macromodelling to study dynamic changes of coordinates of reference stations. This method is good enough to determine the effect of ionosphere on the accuracy of GPS-coordinates of stations. For example, used a network of stations ZAKPOS. The main goal of our work was to study the best way is optimal for accurate positioning of the reference station network.